The Implementation of Round Table Method in English Learning Process Toward Students Writing Skill at SMA Negeri 1 Pamona Timur - Tabasi, Yosafat; Wulan, Sri; Tondowala, Irsan Bertinus; Tobondo, Yuyun Alfasius; Tudjuka, Masril Aguswandi; Labesani, Cirtye; Widnyana, I Gusti Agung Gede (Riwayat: Educational Journal of History and Humanities, 2023)
This research aims to find out how the implementation of the round table method can help students in writing at SMA Negeri 1 Pamona Timur. The design of this research used a quantitative approach pre-experiment method with a one-group pre-test post-test design. Thus, the result can be known to be accurate, allowing one to compare the circumstances before treatment. The research results show that there is a significant difference in the score results of student tests in pre-test and post-test. So Ho rejected, and Ha accepted, meaning implementing the round table method XI MIA class impacted writing skills. This research concludes that Implementing the round table method can help students' writing skills at SMA Negeri 1 Pamona Timur. The test result that has been performed indicates that the mean value of the students increased after being treated in the round table methodthe mean value of students at pre-test 75,48 and post-test 84,57.